1999
DOI: 10.1046/j.1463-5224.1999.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative keratitis associated with qualitative tear film abnormalities in cats

Abstract: Three cats with indolent corneal ulcers and one cat with bilateral corneal sequestration and normal aqueous tear production were found to have rapid tear break-up times (BUTs). Tear BUTs in clinically affected cats averaged 2.5 +/- 1.29 s and 2.33 +/- 0.58 s for the right and left eyes, respectively. Palpebral conjunctival biopsies were harvested from consistent sites from each eye of affected cats (n = 7 affected eyes), and age-and breed-matched controls (n = 2 unaffected eyes). Light microscopy revealed a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 23 publications
(37 reference statements)
1
46
0
Order By: Relevance
“…6 Rapid TFBUT suggests an unstable tear film and has been reported for cats with conjunctivitis, [18][19][20] chronic nonhealing ulcers, 15 and corneal sequestra 15,16 as well as those previously infected with FHV-1. 19 In the present study, TFBUT (median, 12.4 seconds; 95% CR, 9.1 to 17.7 seconds) was shorter than TFBUTs reported in other studies 16,18,19,38 (mean, 13.5 to 21 seconds).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…6 Rapid TFBUT suggests an unstable tear film and has been reported for cats with conjunctivitis, [18][19][20] chronic nonhealing ulcers, 15 and corneal sequestra 15,16 as well as those previously infected with FHV-1. 19 In the present study, TFBUT (median, 12.4 seconds; 95% CR, 9.1 to 17.7 seconds) was shorter than TFBUTs reported in other studies 16,18,19,38 (mean, 13.5 to 21 seconds).…”
Section: Discussionmentioning
confidence: 70%
“…There is increasing evidence that quantitative and qualitative tear film deficiencies are an important cofactor or cause of some of the most common and frustrating ocular diseases of cats, such as KCS, 6,14 chronic nonhealing corneal ulceration, 15 corneal sequestration, [15][16][17] conjunctivitis, [18][19][20] and keratoconjunctivitis following feline herpesvirus-1 infection. 19,21 Despite this, reference ranges for many of the tests commonly used to assess the human and canine tear film have not been established for healthy cats.…”
mentioning
confidence: 99%
“…Even today, the aetiology is unknown, although traumas, prolonged corneal irritation, alterations of the tear film and of the corneal innervation, dystrophy, infections (Herpesvirus) and genetic predisposition would appear to play an important role in determining its onset (Startup, 1988;Pentlarge, 1989;Morgan, 1994;Cullen et al, 1999;La Croix et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic procedure (Cullen et al 2005) and instillation of tropicamide (Margadant et al 2003) deteriorate quantitatively tear secretion in cats. In addition, corneal sequestra, feline herpes virus type 1 (FHV-1), Chammidophola and Mycoplasma infection may produce qualitative tear film abnormalities, principally because the impaired secretion of mucin, which may be attributed to conjunctival scamous metaplasia, inflammation and a decreased amount of conjunctival goblet cells (Cullen et al 1999, Lim & Cullen 2005, Lim et al 2009). In one study, despite the impaired quality of the tear film, assessed by means of tear film break up time and conjunctival biopsies, Lim et al (2009) showed that STT-1 values increased significantly in young cats inoculated experimentally with FHV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anesthetic procedures (Cullen et al 2005), topical instillation of tropicamide (Margadant et al 2003), corneal sequestra (Cullen et al 1999) and feline herpesvirus type 1 infection (Lim & Cullen 2005, Lim et al 2007, 2009) may deteriorate quality and quantity of the tear film.…”
Section: Introductionmentioning
confidence: 99%